Measuring the effectiveness of transport management system (TMS) in monitoring driver behaviour: a case study / Hanafi Mohd Wazir - Mohd Wazir, Hanafi (2024)
The Transport Management System (TMS) is a transformative tool that revolutionizes logistics operations by optimizing route planning, automating carrier selection, and providing real-time visibility. Controlling process fulfillment through the use of technology is highly effective and has a positive impact on businesses in today's digital age. One of the biggest challenges in the transportation and logistics industry is controlling all offsite assets, especially when it comes to managing and monitoring large vehicles driven by company drivers. The use of TMS is very suitable for controlling the driver's posture and driving style. This study to assess the effectiveness of a Transportation Management System (TMS) in monitoring driver behaviour in oil palm industry, propose a framework in measuring the effectiveness of the transportation monitoring system for palm oil industry, and justify the recommendation on how FGV Transport can improve the features of the TMS system in monitoring driver behaviour. Within this framework, it is proposed to use data envelopment analysis (DEA) techniques to identify inputs and outputs as indicators of effectiveness. The data used in this study comes from a selected transportation service company that implemented three transportation management systems since 2010. Some systems track the behavior of drivers while driving, which allow transportation company managers to assess the effectiveness of different routes taken by drivers, contributing to more efficient schedules. Managers can track its efficiency and provide feedback when improvements are needed. The use of TMS for real-time tracking also offers great safety benefits, especially in case of accidents. This study has also recorded data to measure the efficiency of each depot's TMS system from 2009-2010. The results of this study have identified several years and several depots that have recorded efficient and inefficient in measuring the effectiveness of TMS in the operation of each depot. In conclusion, this study has been able to measure the effectiveness of the TMS system to control driver behavior at each depot. In addition, some suggestions and added value have been given in this study for future improvements.